Kandungan Vitamin A dan Protein Bakso Belut di Daerah Istimewa Yogyakarta - Suryani, Yoni; Yuliati, Yuliati; Farida, Yuyun (Jurnal Kedokteran YARSI, 2008)
The objectives of this study were to investigate vitamin A and protein contentsin eel (Monopterus albus) meat balls. Theeel meat balls were made byaspecial addition of tapioca30%, 40%, 50% and 60% of thetotal weight of eel meat. Hedonic test was conducted in order to find the levels of panellist preferences. Friedman test wasemployedto find the effect of tapioca addition on colour, flavour, texture and taste. The content of vitamin A was analysedusing HPLCmethodand proteincontentusing Micro Kjeldahl method. The result revealed that the variation of tapioca addition gavenosignificanteffect on colour performance with the significance level of 1.0. However, it gave significant effect on flavour, texture and taste preferences with the significance level of <0.05. It wasfound that the most favourite eel meat balls was the one with tapioca addition of 50% of the eel meat weight. The average of vitamin A contentwas 2,215.95mg/100 gand protein is 7.2896 mg/100 g on the most favourite eel meat balls.